Analysis of FGGY as a risk factor for sporadic amyotrophic lateral sclerosis. - Es, V; Van Vught, P; Veldink, J; Andersen, P; Birve, A; Lemmens, R; Cronin, S; Van Der Kooi, A; De Visser, M; Schelhaas, H; Hardiman, O; Ragoussis, I; et al. (2009)
A genome-wide association study (GWAS) using pooled DNA samples from 386 sporadic ALS patients and 542 controls from the USA, identified genetic variation in FGGY (FLJ10986) as a risk factor, as well as 66 additional candidate SNPs. Considering the large number of hypotheses that are tested in GWAS, independent replication of associations is crucial for identifying true-positive genetic risk factors for disease. The primary aim of this study was to study the association between FGGY and sporadic ALS in large, homogeneous populations from northern Europe. Genotyping experiments were performed using Illumina Beadchips, Sequenom iPLEX assays and Taqman technology on large case-control series from The Netherlands, Belgium, Sweden and Ireland (total: 1883 sporadic ALS patients and 2063 controls). No significant association between sporadic ALS and the six previously reported associated SNPs in FGGY was observed: rs6700125 (p =0.56), rs6690993 (p =0.30), rs10493256 (p =0.68), rs6587852 (p =0.64), rs1470407 (p =0.28) and rs333662 (p =0.44). Screening of the additional candidate loci did not yield significant associations either, with the lowest p-value in joint analysis for rs7772593 (p =0.14). We concluded that common genetic variation in FGGY is not associated with susceptibility to sporadic ALS in genetically homogeneous populations from northern Europe.